Dynamic postural stability, is associated with competitive level, in youth league soccer players. (January 2019) - Pau, Massimiliano; Porta, Micaela; Arippa, Federico; Pilloni, Giuseppina; Sorrentino, Marco; Carta, Marco; Mura, Mauro; Leban, Bruno
Abstract: Objectives: To assess the effect of competitive level on dynamic postural stability in young elite and sub-elite soccer players. Design: Cross-sectional study. Setting: Laboratory. Participants: Fifty-four male soccer players of Under 16 and Under 17 categories (mean age 15.9 ± 0.6), divided into two groups who regularly compete at national (n = 28) and regional (n = 26) levels. Main outcome measures: Dynamic Postural Stability Index (DPSI) and vertical Time to Stabilization (vTTS) for a forward-jump landing. Static postural sway was calculated on the basis of center-of-pressure trajectories for a 20 s one-legged stance. Results: Players at national level exhibit better dynamic postural control than those at regional level, as indicated by the significantly lower DPSI (0.327 vs. 0.373, p < 0.001) and vTTS (0.887 vs. 1.158 s, p = 0.003). In contrast, no differences between groups were found in any of the postural sway parameters for the static test. Conclusions: Young soccer players at national level are characterized by better balance performance in terms of faster and more efficient stabilization after a forward jump, while one-leg static standing tests appear not challenging enough to reveal differences in balance abilities associated with the combination of superior technical and physical features. Highlights: We analyzed balance in young soccer players of national and regional level. Dynamic Postural Stability Index and Time to Stabilization were computed. Players of national level exhibit significantly lower DPSI and TTS. No differences were found in static postural sway.